Strategic People Management Challenges in the Implementation of the Red and White Village Cooperative Program in Indonesia - Yosi Muhaemin (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
The Red and White Village Cooperative Program represents a major national initiative designed to strengthen rural economic institutions and promote inclusive local development in Indonesia. The rapid establishment of village cooperatives across the country has generated complex organizational challenges related to human resource readiness, governance arrangements, and institutional coordination. This study examines these challenges through the analytical perspective of strategic people management. An empirical qualitative design was employed using secondary data derived from policy documents, institutional reports, and scholarly analyses concerning the implementation of village cooperatives. The data were analyzed through qualitative content analysis to identify patterns associated with human capital capacity, participatory governance, and organizational alignment within cooperative institutions. The findings indicate that limitations in managerial competence, uneven participation structures, and fragmented coordination among rural economic institutions significantly influence program sustainability. Strengthening leadership capacity, developing participatory governance mechanisms, and improving policy alignment with local economic ecosystems are essential for ensuring effective cooperative management. The study contributes to the literature by highlighting the strategic role of human-centered institutional management in supporting sustainable rural cooperative development.